Online reviews in tourism and hospitality industry: a meta-analytical perspective. (15th April 2023) - Dewani, Prem Prakash
Marketers' quest to understand the effect of online reviews on consumer behaviour in general and in the tourism industry, in particular, has witnessed several studies in the recent past. However, some of these research findings are contradictory, which leads to confusion amongst researchers and practitioners. In this study, we conduct meta-analysis of 39 studies comprising 97 effect sizes and 18, 084 observations to resolve these inconsistencies. Based on the Stimulus-Organism-Response framework, we specify the stimulus, organism, and response factors in context of online reviews. We contribute to the existing marketing literature by explaining the process through which online reviews influence travellers' behavioural intention. Further investigation of methodological, contextual, and cultural moderators not only uncovers the causes of inconsistencies but also provides some useful guidelines for future research. We also enlist insights for online review platforms, which can be utilised to enhance the navigation and usability of the platforms.